Answer:
![\huge\boxed{B=6}](https://img.qammunity.org/2021/formulas/mathematics/college/unnx3mrelippgronqw7akal7efaakg78rh.png)
Explanation:
They are two way to solution.
METHOD 1:
Factor the polynomial on the left side of the equation:
![2x^2+4xy-48y^2=2(x^2+2xy-24y^2)=2(x^2+6xy-4xy-24y^2)\\\\=2\bigg(x(x+6y)-4y(x+6y)\bigg)=2(x+6y)(x-4y)](https://img.qammunity.org/2021/formulas/mathematics/college/lmmwv1lhjeomdipwvfkcip0h10hgf5oi1p.png)
Therefore:
![2x^2+4xy-48y^2=2(x+By)(x-4y)\\\Downarrow\\2(x+6y)(x-4y)=2(x+By)(x-4y)\to\boxed{\bold{B=6}}](https://img.qammunity.org/2021/formulas/mathematics/college/hq1nq7i5r8n3wwdxs1ju9u971kp1acs1va.png)
METHOD 2:
Multiply everything on the right side of the equation using the distributive property and FOIL:
![2(x+By)(x-4y)=\bigg((2)(x)+(2)(By)\bigg)(x-4y)\\\\=(2x+2By)(x-4y)=(2x)(x)+(2x)(-4y)+(2By)(x)+(2By)(-4y)\\\\=2x^2-8xy+2Bxy-8By^2=2x^2+(2B-8)xy-8By^2](https://img.qammunity.org/2021/formulas/mathematics/college/6uknxi25n27ap8xa5ks54zqubr2rizirve.png)
Compare polynomials:
![2x^2+4xy-48y^2=2x^2+(2B-8)xy-8By^2](https://img.qammunity.org/2021/formulas/mathematics/college/xm9arfd25pk4aya2qnxo9sk38ligp41e5g.png)
From here we have two equations:
![2B-8=4\ \text{and}\ -8B=-48](https://img.qammunity.org/2021/formulas/mathematics/college/35eitb9sd1qpgo6b8700lezwsue826k5es.png)
add 8 to both sides
divide both sides by 2
![B=6](https://img.qammunity.org/2021/formulas/mathematics/college/7cylzye6hxbrkji2afqstvgvea8qe2cr85.png)
divide both sides by (-8)
![B=6](https://img.qammunity.org/2021/formulas/mathematics/college/7cylzye6hxbrkji2afqstvgvea8qe2cr85.png)
The results are the same. Therefore B = 6.